The influence of chronic physiological stress on financial health perceptions - Zepp, Phillip Preston (Kansas State University, 2019)
There is limited research on physiological stress in the financial planning field. While the literature shows a clear relationship between physiological stress and physical health, little is known about the relationship between physiological stress and financial health perceptions. With Lazarus and Folkman’s (1984) theory of cognitive appraisal serving as the framework for this study, three multivariate regressions investigated the relationship between chronic physiological stress and financial health perceptions as measured by changes in financial satisfaction, changes in financial strain, and expectations about one’s financial situation in the future. The sample consisted of 703 individuals that were recruited from 2011-2014 to participate in the Midlife in the United States Refresher study. Based on non-imputed data, respondents were evenly split between male and female and between 25 and 76 years old with a mean age of 51 years old. Respondents were also mostly white, working, married, and had some college education. The sample reported mean household income of $71,052 and a net worth of $586,329. The mean salivary cortisol level was 16.06 Nanomoles per litre (nmol/L), and respondents reported better than the median score for self-reported health status. When comparing before the recession to present day, the mean responses from respondents indicated that their financial strain remained about the same, but financial satisfaction declined. Respondents reported better than the median score for expectations about their financial future. An ordinary least squares regression was used to model changes in financial satisfaction. A cumulative logistic regression was used to model changes in financial strain and expectations about one’s future financial situation. The model results provided support for several key hypotheses formed from the theoretical framework. In particular, salivary cortisol, the proxy for chronic physiological stress, had a statistically significant negative relationship with expectations about one’s future financial situation. An increase in chronic physiological stress was associated with lower expectations about the financial future. There was not a statistically significant relationship between salivary cortisol and changes in financial satisfaction or changes in financial strain. Given the sparse physiological stress research that exists in the financial planning field, this study provides researchers and practitioners with new information regarding the impact of chronic physiological stress on financial health perceptions. Measuring physiological stress in a non-experimental setting gives researchers a different approach to understanding the impacts of physiological stress. For practitioners, uncovering the relationship between chronic physiological stress and financial health perceptions might promote the use of stress reductions as part of holistic approach to financial planning.
Keywords: Physiological stress; Chronic physiological stress; Salivary cortisol; Financial health perceptions; Coping